2019
DOI: 10.3390/ijerph16173037
|View full text |Cite
|
Sign up to set email alerts
|

Validity of Wrist-Worn Activity Trackers for Estimating VO2max and Energy Expenditure

Abstract: Activity trackers are a simple and mostly low-priced method to capture physiological parameters. Despite the high number of wrist-worn devices, there is a lack of scientific validation. The purpose of this study was to assess whether the activity trackers represent a valid alternative to gold-standard methods in terms of estimating energy expenditure (EE) and maximum oxygen uptake (VO2max). Twenty-four healthy subjects participated in this study. In total, five commercially available wrist-worn devices were te… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
33
1
5

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 31 publications
(43 citation statements)
references
References 31 publications
1
33
1
5
Order By: Relevance
“…Sartor et al (2013) have argued that many HR-based submaximal test programs are known to underestimate VO 2max because the workload is not high enough to promote adequate parasympathetic withdrawal and concomitant sympathetic activation. The tendency of underestimation was discovered in previous FFT-related studies (Anderson et al, 2019;Passler et al, 2019). Unlike those findings, this study found that the FFT method overestimated VO 2max in both the rowing and running programs.…”
Section: Analysis Of Comparison Between the Fft Methods And Previous Predictive Equationscontrasting
confidence: 84%
See 2 more Smart Citations
“…Sartor et al (2013) have argued that many HR-based submaximal test programs are known to underestimate VO 2max because the workload is not high enough to promote adequate parasympathetic withdrawal and concomitant sympathetic activation. The tendency of underestimation was discovered in previous FFT-related studies (Anderson et al, 2019;Passler et al, 2019). Unlike those findings, this study found that the FFT method overestimated VO 2max in both the rowing and running programs.…”
Section: Analysis Of Comparison Between the Fft Methods And Previous Predictive Equationscontrasting
confidence: 84%
“…However, these equations were developed for the nonathletic population and should be used with caution for well-trained athletes. The findings of this study revealed that the FFT method had a fairly accurate VO 2max estimation for well-trained rowers and paddlers and that the FFT method has been proven to accurately estimate VO 2max in nonathletic populations (college students, healthy adults, and recreational runners; Kraft and Roberts, 2017;Kraft and Dow, 2019;Passler et al, 2019). However, the rowing exercise program was not included.…”
Section: Novelty Analysismentioning
confidence: 88%
See 1 more Smart Citation
“…VO 2max varies over a wide range among individuals, depending on level of aerobic training, genetic makeup, age, health status, and sex. It defines functional aerobic capacity of a single individual in a specific exercise performance and reflects a person’s cardiorespiratory fitness level [ 62 ].…”
Section: Lipids As a Form Of Energy During Exercisementioning
confidence: 99%
“…Dass die aufgezeigte Konkordanzsituation der GF5 durchaus auch auf andere marktrelevante WD übertragbar ist, zeigen die aktuellen Daten von Passler et al (2019). Die in der vergleichenden Arbeit von Düking et al (2020) ermittelten und zum Teil durchaus ermutigenden linearen Befunde zur Validität ebensolcher WD sollten im Hinblick auf den hier explizierten Reliabilitätsaspekt der Konkordanz (aufgrund des abweichenden methodisch-analytischen Zuganges) in jedem Falle nicht hypothesenleitend verwendet werden.…”
Section: Zusammenfassung Einordnung Und Praktische Implikationunclassified